2011
DOI: 10.1038/pcan.2011.65
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and risk of BPH: a meta-analysis

Abstract: BACKGROUND: Epidemiological studies have reported conflicting results relating obesity to BPH. A meta-analysis of cohort and case-control studies was conducted to pool the risk estimates of the association between obesity and BPH.METHODS: Eligible studies were retrieved by both computer searches and review of references. We analyzed abstracted data with random effects models to obtain the summary risk estimates. Dose-response meta-analysis was performed for studies reporting categorical risk estimates for a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 54 publications
2
46
0
1
Order By: Relevance
“…Although there is conflicting evidence, smoking [49], exercise [50], and a low-fat diet [51] have all been associated with decreased PSA and BMI, and high alcohol intake and benign prostatic hypertrophy [52] have been associated with increased PSA and BMI [53]. These variables were not considered in this study, but these associations would indicate a positive relationship between BMI and PSA which is not observed in this study; thus, it is unlikely that the observed BMI–PSA relationship was biased away from the null by any of these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is conflicting evidence, smoking [49], exercise [50], and a low-fat diet [51] have all been associated with decreased PSA and BMI, and high alcohol intake and benign prostatic hypertrophy [52] have been associated with increased PSA and BMI [53]. These variables were not considered in this study, but these associations would indicate a positive relationship between BMI and PSA which is not observed in this study; thus, it is unlikely that the observed BMI–PSA relationship was biased away from the null by any of these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Although our results clearly point out that increased BMI and weight at early-middle age are associated with an increased risk for aggressive PCa disease, it is currently unclear if anthropometrics significantly adds to currently established risk prediction models. Further, we did not investigate if anthropometrics measured at different time-points in life were also associated with BPH (benign prostate hyperplasia) (42), which may potentially cause a detection bias.…”
Section: Discussionmentioning
confidence: 99%
“…With some studies suggesting that obese men are more likely to have LUTS [3,4], weight reduction could be one such intervention. Body size and composition have long been hypothesized to influence the risk of prostate hyperplasia [5]. While some data have suggested that weight gain worsens LUTS, few data are available to address whether the reverse is true, i.e., if weight loss can improve LUTS.…”
Section: Introductionmentioning
confidence: 99%